A Multifaceted Hypnosis Smoking-Cessation Program: Enhancing Motivation and Goal Attainment. Issue 3 (3rd July 2017) - Green, Joseph P.; Lynn, Steven Jay
Abstract: Smoking cessation remains a major health priority. Despite public campaigns against smoking and widespread availability of smoking-cessation treatments, many people continue to smoke. The authors argue that the "problem of motivation, " that is, suboptimal or fluctuating motivation to resist smoking urges and to comply with the demands of treatment, commonly undermines treatment seeking and adherence, appreciably reducing the success rates of smoking-cessation programs. The authors describe the history of the Winning Edge smoking-cessation program and discuss ways to enhance motivation before, during, and after formal treatment. They illustrate how hypnotic suggestions, administered in the context of their program, can promote cognitive, behavioral, and emotional commitment to treatment and enhance motivation to live a smoke-free life.